2018
DOI: 10.1016/j.jcma.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor size on the prognosis of hepatocellular carcinoma in patients who underwent liver resection

Abstract: Tumor size ≥5 cm might be a good predicting factor for death and early recurrence when considering death as a competing risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 39 publications
6
34
0
1
Order By: Relevance
“…However, we extended the observation to the post-operative follow-up period. We identified that tumor size may determine early HCC recurrence, which was in line with previous report 17 . Imperatively, we demonstrated that low MICA levels in the cancer tissue may play a critical biological role.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we extended the observation to the post-operative follow-up period. We identified that tumor size may determine early HCC recurrence, which was in line with previous report 17 . Imperatively, we demonstrated that low MICA levels in the cancer tissue may play a critical biological role.…”
Section: Discussionsupporting
confidence: 92%
“…A stepwise logistic regression analysis was performed to evaluate the independent factors associated with high levels of MICA expression in the tumor tissue. To avoid the issue of incomplete resection, patients with recurrent HCC within six months after surgery were excluded when judging the factors predictive of HCC recurrence 17 . Kaplan–Meier analysis and the log-rank test were performed by comparing the differences in HCC recurrence between the determining factors.…”
Section: Methodsmentioning
confidence: 99%
“…In Cox regression analyses, EXO1 expression was (univariate) or tended to be (multivariate) an independent risk factor, while gender and tumor size were definite independent risk factors. As a widely used marker for routine surveillance and noninvasive diagnosis of HCC, high serum AFP levels (≥ 20µg/L) play an important role in predicting high mortality among patients with tumor size ≥ 5 cm [36]. However, prognostic markers for patients with no AFP expression (< 20µg/L) are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Production of AFP in tumors us often found in the germ cell tumors, particularly yolk sac tumor [ 4 , 5 ]. AFP is also secreted in other tumors such as hepatocellular carcinoma and testicular carcinoma [ 6 ]. Epithelial ovarian cancers had been rarely reported to secrete AFP [ 7 , 8 ], and AFP-producing EOCs are also extremely rare.…”
Section: Discussionmentioning
confidence: 99%